2016
DOI: 10.14260/jemds/2016/305
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Following Lower Segment Caesarean Section in a Tertiary Care Hospital

Abstract: AIM OF THE STUDYTo identify infection rates and risk factors associated with Surgical Site Infection (SSI) following Caesarean Section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…Incidence of SSI following caesarean section in the present study was found to be 4% which was found to be in accordance with studies of Kondakasseril et al and Vallejo et al 7,8 Kondakasseril et al carried out a case control study amongst all women who delivered by caesarean section and found that the overall wound infection rate in the study was 3.5%, (50) among 1410 Lower Transverse caesarean section. 7 Vallejo et al, conducted a retrospective, case-controlled, time-matched, quality assurance electronic medical record (EMR) analysis to determine the incidence of surgical site infection (SSI) after caesarean delivery (CD) and identify the risk factors in a rural population and concluded that the incidence of SSI after CD was 7.0%. 8…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Incidence of SSI following caesarean section in the present study was found to be 4% which was found to be in accordance with studies of Kondakasseril et al and Vallejo et al 7,8 Kondakasseril et al carried out a case control study amongst all women who delivered by caesarean section and found that the overall wound infection rate in the study was 3.5%, (50) among 1410 Lower Transverse caesarean section. 7 Vallejo et al, conducted a retrospective, case-controlled, time-matched, quality assurance electronic medical record (EMR) analysis to determine the incidence of surgical site infection (SSI) after caesarean delivery (CD) and identify the risk factors in a rural population and concluded that the incidence of SSI after CD was 7.0%. 8…”
Section: Discussionsupporting
confidence: 91%
“…21 Kondakasseril et al carried out a case control study amongst all women who delivered by caesarean section and found that the overall superficial infection was seen in 36 (72%) and deep infection in 12 (24%) and Organ/Space SSI in 2 (4%). 7 In the present study, we found that majority of SSI postcaesarean section occurred between 4 th to 10 th postoperative day. The study carried out by Bhadauria et al to find out the incidence of post-operative wound infection among the elective and emergency obstetrics and gynaecological abdominal surgeries showed the appearance of infection between 6 th and 10 th postoperative days in more than half of the population.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Devi and Durga [11] and Kawakita and Landy [15] observed that 1 st time mothers who underwent primary cesarean has significant association of developing SSI which is in contrast to finding in the present study. SSI was evenly distributed among both nulliparous and multipara as per Kondakasseril et al [7].…”
Section: Paritymentioning
confidence: 88%
“…Wodajo et al [5] 11 Mpogoro et al [6] 10.9 Kondakasseril et al [7] 4.4 Vijayan et al [8] 4.1 De et al [9] 24.…”
Section: Authors Incidence (%)mentioning
confidence: 99%